Event-based bipartite consensus of second-order discrete-time multi-agent systems with matrix-weighted signed networks. Issue 4 (March 2023) - Miao, Suoxia; Su, Housheng; Wang, Dong
Abstract: This article researches the bipartite consensus for discrete-time second-order multi-agent systems on matrix-weighted signed networks, which can describe the inter-dependencies of multidimensional states among states. So as to save limited communication resources, based on the matrix-weighted combined measurements of the position and velocity states, a matrix-weighted event-triggered control algorithm is designed. With the help of the stability theory, variable transformation and the inequality technique, the bipartite consensus conditions which are based on coupling gains, discrete interval, the parameters in the event-triggered rule and communication topology are obtained. Furthermore, the conditions to avoid the controller updating in each discrete-time are supplied. At last, a simulation example is offered to demonstrate the theoretical results.